Left Atrial Plasty in Surgical Treatment of Combined Mitral-Aortic-Tricuspid Valve Diseases Complicated by Left Atrial Dilation - Popov, Volodymyr V.; Bolshak, Oleksandr O. (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To study the possibilities of various techniques of the left atrial (LA) plasty in the correction of combined mitral-aortic-tricuspid valve diseases (cMATVD) in the presence of left atrial dilation (LAD). Materials and methods. The analysis included the results of surgical treatment of 360 patients with cMATVD combined with LAD, who were operated on at the National Amosov Institute of Cardiovascular Surgery from January 1, 2006 to January 1, 2023. The main group consisted of 73 patients who underwent cMATVD correction combined with original triangular plasty of LA. The comparison group included 287 patients who underwent only cMATVD correction in the presence of concomitant LAD. Results. Of the 73 operated patients in the main group, 3 died at the hospital stage (mortality rate 4.1%). The dynamics of echocardiographic parameters at the stages of treatment were as follows: left ventricular (LV) end- systolic index (ml/m2): 69.1 ± 12.1 (before surgery), 59.3 ± 8.5 (after surgery), and 48.4 ± 9.5 (long-term period); LV ejection fraction (%): 51.0 ± 5.0 (before surgery), 54.0 ± 5.0 (after surgery), and 56.0 ± 4.0 (long-term period); LA diameter (mm): 64.8 ± 4.1 (before surgery), 50.3 ± 2.1 (after surgery), and 51.2 ± 2.2 (long-term period). Of the 287 operated patients in the comparison group, 9 died (mortality rate 3.1%). The dynamics of echocardiographic parameters at the stages of treatment were as follows: LV end-systolic index (ml/m2): 68.3 ± 11.3 (before surgery), 60.4 ± 9.3 (after surgery), and 52.7 ± 7.2 (remote period); LV ejection fraction (%): 52.0 ± 5.0 (before surgery), 53.0 ± 5.0 (after surgery), and 50.0 ± 4.0 (remote period); LA diameter (mm): 65.5 ± 3.7 (before surgery), 64.1 ± 3.3 (after surgery), and 72.5 ± 2.8 (remote period). In the remote period, thromboembolic complications occurred in 5 (7.7%) patients of the main group (1 severe, 1 mild, and 3 fatal) and 25 (9.3%) patients of the comparison group (10 severe, 6 mild, and 9 fatal). The thromboembolic complications rates indicate the advisability of LA plasty simultaneously with resection of its appendage. Conclusions. In the correction of LAD, all plastic reconstructions of the dilated LA are low-traumatic and effective procedures that lead to a significant improvement in the morphometry of the LA both at the hospital stage and in the remote period. The methods are associated with low risk of hospital mortality, as well as a low level of thromboembolic complications in the remote period. In all methods of LA plasty, its appendage was resected, which also excluded conditions for thrombus formation.